ANALISIS KUALITAS PENGEMASAN VAKUM IKAN BEKU DENGAN METODE SIX SIGMA (Studi Kasus di PT X, Pasuruan Jawa Timur) - Sucipto Sucipto; Retno Astuti; Ayuningtyas Megawati (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Quality control is carried out as one of the strategies to measure the capability of the production process. This is to identify the factors that cause products no standardized and propose improvements. During this time, there are often problems in the vacuum packaging of frozen fish. The analysis method used Six Sigma with the stages Define, Measure, Analyze and Improve. The results showed that the Critical to Quality (CTQ) of packaging process is leaking packaging, but the process is working well and it is above the industry average in Indonesia. It can be seen the value of Sigma and the final yield. Packaging leaked based on a fishbone diagram and Failure Modes and Effects Analysis (FMEA) is caused by human factors.The proposed improvement is by monitoring, guidance, and training of human resources. This is done so that the process can be towards the target 6-Sigma.